The cubic-to-orthorhombic phase transition: rigidity and non-rigidity properties in the linear theory of elasticity - Rüland, Angkana (Archive for rational mechanics and analysis, 2016)
In this paper we investigate the cubic-to-orthorhombic phase transition in the framework of linear elasticity. Using convex integration techniques, we prove that this phase transition represents one of the simplest three-dimensional examples in which already the linearised theory of elasticity displays non-rigidity properties. As a complementary result, we demonstrate that surface energy constraints rule out such highly oscillatory behaviour. We give a full characterization of all possibly emerging patterns for generic material parameters.
Gesehen am 27.05.2021